2004
DOI: 10.2337/diacare.27.8.1942
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Forearm Blood Flow in Children and Adolescents With Type 1 Diabetes (Measured by Near-Infrared Spectroscopy)

Abstract: OBJECTIVE -The aim of this study was to measure forearm blood flow (FBF) to detect any possible changes that might indicate vascular disorders in children and adolescents with type 1 diabetes.RESEARCH DESIGN AND METHODS -FBF was measured by near-infrared spectroscopy (NIRS), venous occlusion at rest, and after handgrip exercise. A total of 40 children and adolescents with type 1 diabetes and 40 healthy children and adolescents (6 -18 years) were matched for age and sex for comparison.RESULTS -In the diabetic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 28 publications
(32 reference statements)
3
30
0
Order By: Relevance
“…VO 2 decreased with increasing age. FBF decreased with increasing age, too, as we have recently reported [6].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…VO 2 decreased with increasing age. FBF decreased with increasing age, too, as we have recently reported [6].…”
Section: Discussionsupporting
confidence: 74%
“…Nevertheless, most studies on muscle oxygenation and hemodynamics were performed on healthy adults and adult patients [1,4,7] and on term and preterm neonates [8,9]. In a recent study we analyzed FBF in children and adolescents with type I diabetes and healthy children and adolescents [6].…”
Section: Near Infrared Spectroscopy (Nirs) Is a Relatively Newmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we found that a−vO 2 was the same in diabetic as in non-diabetic adolescents. Further investigations are needed to clarify the contribution of peripheral function to the decreased aerobic capacity of diabetic adolescents, since impaired endothelial function has already been observed in this population [10]. This is a relatively small study and the results should be viewed as preliminary data.…”
Section: Discussionmentioning
confidence: 90%
“…Functional microvascular disturbances in the nail fold of the great toe in type 1 diabetic patients, evaluated by capillary blood flow velocity, have been shown to precede late diabetic complications [3,4] and to be related to poor metabolic control [5]. Nevertheless, the presence of microvascular alterations in uncomplicated type 1 diabetes is still a controversial matter [1,[6][7][8]. The present study assessed microvascular function using skin capillary recruitment during post-occlusive reactive hyperemia, which is related to endothelium-dependent vasodilatation at the precapillary level [9,10], in the upper and lower extremities of patients with type 1 diabetes without chronic complications under routine clinical care.…”
Section: Introductionmentioning
confidence: 99%